An innovative framework to determine the implementation level of personalized medicine: A systematic review - Aguilera-Cobos, Lorena; García-Sanz, Patricia; Rosario-Lozano, María Piedad; Claros, M. Gonzalo; Blasco-Amaro, Juan Antonio (Frontiers in Public Health, 2023)
Abstract Background: Personalized medicine (PM) is now the new frontier in patient care. The application of this new paradigm extends to various pathologies and different patient care phases, such as diagnosis and treatment. Translating biotechnological advances to clinical routine means adapting health services at all levels is necessary. Purpose: This article aims to identify the elements for devising a framework that will allow the level of PM implementation in the country under study to be quantitatively and qualitatively assessed and that can be used as a guideline for future implementation plans. Methods: A systematic review was conducted per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The research question was: What are the domains for determining the level of implementation of PM at the national level? The domains for assessing the degree of PM implementation, which would form the framework, were established. Results: 19 full-text studies that met the inclusion criteria were peer-selected in the systematic review. From all the studies that were included, 37 elements -encompassed in 11 domains- were extracted to determine the degree of PM implementation. These domains and their constituent elements comprise the qualitative and quantitative assessment framework presented herein. Each of the elements can be assessed individually. On the other hand, the domains were standardized to all have the same weight in an overall assessment. Conclusions: A framework has been developed that takes a multi-factorial approach to determine the degree of implementation of PM at the national level. This framework could also be used to rank countries and their implementation strategies according to the score they receive in the application of the latter. It could also be used as a guide for developing future national PM implementation strategies.